In vitro Comparative Study of Compressive Strength of DifferentTypes of Composite Resins in Different Periods of Time: Deposition of nano-crystalline fluorhydroxyapatite coatings on titanium substrates via sol-gel method - Banava, Sepideh; Salehyar, Saman (Iranian Journal of Pharmaceutical Sciences, 2008)
To evaluate the ultimate compressive strength of five composite resins after 1 hour,24 hours, 7 days and 1 month. Twenty four cylindrical 4 mm×8mm specimens ofeach commonly used composite resins in posterior region (Nulite-F , Z250 , P60,Biscore, Tetric ceram HB) were prepared. Each group of composite resins weredivided into four time groups of 1 h, 24 h, 7 days and 1 month. All of specimensstored in an incubator with 37 °C. After each period of time all of the specimenswere tested by Zwick/Roell Z020 (Germany) for ultimate compressive strength atcross head speed of 0.5 cm/min. Results were analyzed by ANOVAand Scheffe test.P60 and Z250 had the highest and Nulite-F and Tetric ceram HB had the lowestcompressive strength at all the times. The difference between these two groups wasstatistically significant (p<0.05). The results of the Biscore was steady among theother groups. It is suggested to use Z250 or P60 in posterior restorations instead ofthe other composite resins tested.